Comprehensive analysis of translation from overexpressed circular RNAs reveals pervasive translation from linear transcripts. Issue 18 (21st September 2020) - Ho-Xuan, Hung; Glažar, Petar; Latini, Claudia; Heizler, Kevin; Haase, Jacob; Hett, Robert; Anders, Marvin; Weichmann, Franziska; Bruckmann, Astrid; Van den Berg, Debbie; Hüttelmaier, Stefan; Rajewsky, Nikolaus; et al.
Abstract: Circular RNAs (circRNAs) encompass a widespread and conserved class of RNAs, which are generated by back-splicing of downstream 5′ to upstream 3′ splice sites. CircRNAs are tissue-specific and have been implicated in diseases including cancer. They can function as sponges for microRNAs (miRNAs) or RNA binding proteins (RBPs), for example. Moreover, some contain open reading frames (ORFs) and might be translated. The functional relevance of such peptides, however, remains largely elusive. Here, we report that the ORF of circZNF609 is efficiently translated when expressed from a circZNF609 overexpression construct. However, endogenous proteins could not be detected. Moreover, initiation of circZNF609 translation is independent of m 6 A-generating enzyme METTL3 or RNA sequence elements such as internal ribosome entry sites (IRESs). Surprisingly, a comprehensive mutational analysis revealed that deletion constructs, which are deficient in producing circZNF609, still generate the observed protein products. This suggests that the apparent circZNF609 translation originates from trans-splicing by-products of the overexpression plasmids and underline that circRNA overexpression constructs need to be evaluated carefully, particularly when functional studies are performed.